DESIGN PRINCIPLES FOR TODAY’S MICROPROCESSORS - Oluwamuyiwa A., Noiki; Adekunle, Y.A (European Scientific Journal, ESJ, 2013)
This article presents an overview of issues to address before embarking on the production of any processor. Processors used in systems must provide highly energy-efficient operation, with regards to the importance of battery utilization, without compromising high performance when the user requires it. Today’s microprocessors are the powerful descendants of the von Neumann computer. The so called von Neumann architecture is characterized by a sequential control flow resulting in a sequential instruction stream. A program counter addresses the next instruction if the preceding instruction is not a control instruction such as a jump, branch, subprogram call or return. An instruction is coded in an instruction format of fixed or variable length, where the op-code is followed by one or more operands that can be data, addresses of data, or the address of an instruction in the case of a control instruction. The op-code defines the types of operands. Code and data are stored in a common storage that is linear, addressed in units of memory words (bytes, words, etc.).